Species of the genus Epilobium (Onagraceae) in plant communities in Ukraine - Fedoronchuk M.M. (Ukrainian Botanical Journal, 2021)
To assess the coenotic peculiarities of species of the genus Epilobium (Onagraceae), in particular their coenotic amplitudes in the syntaxa of vegetation of Ukraine, 986 relevés from literature sources were analyzed. The names of syntaxa are provided in accordance with the Prodromus of the vegetation of Ukraine. Species of the genus Epilobium are widely represented in many plant communities and participate in the formation of natural, semi-natural and ruderal coenoses, where they are often diagnostic or characteristic species of associations, alliances, orders and classes of vegetation, or only present in their floristic composition. Epilobium species are present in 28 classes, which is evidence of their broad coenotic amplitudes and representation in different vegetation types: wetland, grassland, halophytic, forest, shrubs, chasmophytic, alpine, and anthropogenic (synanthropic). The widest coenotic amplitudes were revealed in such species as: E. hirsutum, E. palustre, E. angustifolium, E. parviflorum, E. tetragonum, E. montanum, E. alsinifolium, and E. collinum. According to the range of coenotic amplitude, all species can be subdivided into three groups: hemistenotopic, which occur within one class (E. adenocaulon, E. dodonaei, E. lamyi, E. nutans), hemi-eurytopic (within two or three classes) – E. alpestre, E. roseum, and eurytopic (within more than three classes) – E. alsinifolium, E. angustifolium, E. collinum, E. hirsutum, E. montanum, E. palustre, E. parviflorum, E. tetragonum. As for participation of species in the coenosis, the vast majority of them are assectators, and only a small portion can be temporary edificators (in some groups, at certain successive stages of vegetation development: E. angustifolium). Plants of Epilobium species can reproduce rapidly, both vegetatively and by seeds, which promotes their active colonization of new habitats. However, they usually do not tolerate increased shading and coenotic competition with other plant species, so their strategy is mainly ruderal.